Effects of Caffeine Ingestion on Anaerobic Capacity in a Single Supramaximal Cycling Test - Miyagi, Willian E.; Bertuzzi, Romulo C.; Nakamura, Fabio Y.; de Poli, Rodrigo A. B.; Zagatto, Alessandro M. (Frontiers in Nutrition, 2018)
The aim of this study was to verify the effects of caffeine on anaerobic capacity estimated by the sum of the estimated glycolytic [E[La]] and phosphagen [EPCr] metabolism based on blood lactate and excess post-oxygen consumption responses (AC[La-]+EPOCfast). Fourteen male cyclists were submitted to a graded exercise test to determine the maximal oxygen uptake ("V" ̇"O" _"2max" ) and intensity associated with(" V" ) ̇"O" _"2max" (i"V" ̇"O" _"2max" ). Subsequently, the participants performed two supramaximal efforts at 115% of i"V" ̇"O" _"2max" to determine the AC[La-]+EPOCfast, after previous supplementation with caffeine (6 mg·kg-1) or a placebo (dextrose), in a cross over, randomized, double blind, and placebo-controlled design. The time to exhaustion was higher in the caffeine (186.6±29.8s) than the placebo condition (173.3±25.3s) (p=0.006) and significant correlations were found (r=0.86; P=0.00008). Significant differences were not found between AC[La-]+EPOCfast values from the placebo (4.06±0.83L and 55.2±5.7mL·kg-1) and caffeine condition (4.00±0.76L and 54.6±5.4mL·kg-1), however significant correlations were observed only for absolute values (r=0.74; p<0.002). The E[La] and EPCr also presented no significant differences and were significantly correlated. We conclude based on the overall comparison of mean values between two treatments that acute caffeine ingestion improves the time to exhaustion but does not affect anaerobic capacity estimation; however, the effect of caffeine on the performance and anaerobic capacity depend on the individual.